2016
DOI: 10.1113/jp272152
|View full text |Cite
|
Sign up to set email alerts
|

Diacylglycerol‐mediated regulation of Aplysia bag cell neuron excitability requires protein kinase C

Abstract: Following synaptic input, the bag cell neurons of Aplysia undergo a long-term afterdischarge of action potentials to secrete egg-laying hormone and initiate reproduction. Early in the afterdischarge, phospholipase C (PLC) hydrolyses phosphatidylinositol-4,5-bisphosphate into inositol trisphosphate (IP3 ) and diacylglycerol (DAG). In Aplysia, little is known about the action of DAG, or any interaction with IP3 ; thus, we examined the effects of a synthetic DAG analogue, 1-oleoyl-2-acetyl-sn-glycerol (OAG), on w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 105 publications
2
15
0
Order By: Relevance
“…Last, ethanol (100% v/v) was used to dissolve N-ethylmaleimide (NEM; 50 mM; E3876, Sigma-Aldrich). The final concentration of DMSO or ethanol in the bath was Յ0.2% (v/v), which in control experiments here or in prior studies was found to have no effect on bag cell neuron holding current, membrane conductance, or membrane potential (Hickey et al, 2010(Hickey et al, , 2013Tam et al, 2011;Sturgeon and Magoski, 2016;White et al, 2018).…”
Section: Methodsmentioning
confidence: 87%
See 2 more Smart Citations
“…Last, ethanol (100% v/v) was used to dissolve N-ethylmaleimide (NEM; 50 mM; E3876, Sigma-Aldrich). The final concentration of DMSO or ethanol in the bath was Յ0.2% (v/v), which in control experiments here or in prior studies was found to have no effect on bag cell neuron holding current, membrane conductance, or membrane potential (Hickey et al, 2010(Hickey et al, , 2013Tam et al, 2011;Sturgeon and Magoski, 2016;White et al, 2018).…”
Section: Methodsmentioning
confidence: 87%
“…With the slow-phase, phospholipase C cleaves PIP 2 into IP 3 and DAG (Fink et al, 1988). DAG gates a second, voltageindependent cation channel, with a distinct pharmacology and reversal potential of ϳϪ20 mV (Sturgeon and Magoski, 2016). This channel may be similar to TRPC3/6/7 channels, which are well established as being activated by DAG (Hofmann et al, 1999;Okada et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of phosphatidylinositols in Aplysia neuronal membranes was established based on lipid profile studies (Piomelli et al, 1987) and the liberation of arachidonic acid from PIP 2 by PLC (Carlson and Levitan, 1990), as well as previous whole-cell experiments, suggesting that PLC activity can influence a voltageindependent bag cell neuron cation current (Sturgeon and . Given that PLC is activated during the afterdischarge and results in the formation of IP 3 and DAG (Fink et al, 1988), we investigated the effect of these metabolites on the voltagedependent cation channel.…”
Section: Plc-mediated Pip 2 Breakdown Products Modulate Cation Channel Activitymentioning
confidence: 99%
“…Ongoing research indicates that DAG and IP 3 also directly gate or modulate various ion channels, including gap junctions and inwardly rectifying K ϩ channels, as well as native and transient receptor potential (TRP) nonselective cation channels (Albert and Large, 2003;Gamper and Shapiro, 2007;Decrock et al, 2013). TRP channels are a diverse cation channel superfamily, some of which are voltage-dependent, permeable to both monovalent and divalent cations, sensitive to intracellular Ca 2ϩ , and play a role in a myriad of cellular processes (Clapham, 2003;Montell, 2005;Hardie, 2007). Both PIP 2 and DAG directly gate TRP channels, either by modulation of the lipid microenvironment surrounding the channels or via classic agonist-like binding to the channel (Hofmann et al, 1999;Hansen, 2015;Hille et al, 2015).…”
Section: Introductionmentioning
confidence: 99%